2011
DOI: 10.1097/tp.0b013e31820f08e8
|View full text |Cite
|
Sign up to set email alerts
|

The 5-Year Outcome of ABO-Incompatible Kidney Transplantation With Rituximab Induction

Abstract: In the long term, inclusion of rituximab in the preoperative regimen yielded an even better outcome than that of ABO-CKT and rituximab-untreated ABO-IKT, without any increase in the risk of infection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
54
2
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
4
2

Relationship

0
10

Authors

Journals

citations
Cited by 119 publications
(60 citation statements)
references
References 15 publications
2
54
2
2
Order By: Relevance
“…Oettl et al (11) detected BK viremia in 7 of their 10 ABO-incompatible recipients in a prospective analysis, but no BKVAN was seen on serial protocol biopsy. Large series of ABO-incompatible patients have not reported on the incidence of BK viremia or nephropathy, including the Japanese, who have the most experience with ABO-incompatible (19,20). However, lack of reporting does not imply lack of association.…”
Section: Discussionmentioning
confidence: 99%
“…Oettl et al (11) detected BK viremia in 7 of their 10 ABO-incompatible recipients in a prospective analysis, but no BKVAN was seen on serial protocol biopsy. Large series of ABO-incompatible patients have not reported on the incidence of BK viremia or nephropathy, including the Japanese, who have the most experience with ABO-incompatible (19,20). However, lack of reporting does not imply lack of association.…”
Section: Discussionmentioning
confidence: 99%
“…However, RTX can also ameliorate chronic inflammatory diseases mediated by T and B cells, such as rheumatoid arthritis (8) and multiple sclerosis (9), suggesting that the therapeutic effect of RTX not solely depends on inhibition of antibody production. In renal transplantation, RTX is used successfully in ABOincompatible (ABOi) transplantation (10), in desensitization protocols (11), and for treatment of antibody-mediated rejection (12).…”
Section: Introductionmentioning
confidence: 99%
“…A recent study examining the role of rituximab as an induction agent found no benefit compared to placebo [70]. However, it does play a role as a desensitizing agent in patients with preformed donor specific antibodies (DSA), in conjunction with total plasmapheresis and/or intravenous immunoglobulin (IVIG) [71,72].…”
Section: Applicationsmentioning
confidence: 99%